2005
DOI: 10.1103/physrevd.71.021302
|View full text |Cite
|
Sign up to set email alerts
|

Big bang nucleosynthesis with a new neutron lifetime

Abstract: We show that the predicted primordial helium production is significantly reduced when new measurements of the neutron lifetime and the implied enhancement in the weak reaction rates are included in big-bang nucleosynthesis. Therefore, even if a narrow uncertainty in the observed helium abundance is adopted, this brings the constraint on the baryon-to-photon ratio from BBN and the observed helium into better accord with the independent determination of the baryon content deduced from the WMAP spectrum of power … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 33 publications
(35 reference statements)
2
102
0
2
Order By: Relevance
“…Increasing Newton's constant enhances the universal expansion rate, and then leads to larger helium and deuterium abundances produced at BBN epoch. We have re-examined this effect including the latest experimental data on the neutron lifetime [15,27]. We found that the experimental value G N (ξ = 1) is now quite consistent with the observed abundances of primordial light elements, and the variation of Newton's constant is tightly constrained to 0.95 < ∼ ξ < ∼ 1.01.…”
mentioning
confidence: 98%
“…Increasing Newton's constant enhances the universal expansion rate, and then leads to larger helium and deuterium abundances produced at BBN epoch. We have re-examined this effect including the latest experimental data on the neutron lifetime [15,27]. We found that the experimental value G N (ξ = 1) is now quite consistent with the observed abundances of primordial light elements, and the variation of Newton's constant is tightly constrained to 0.95 < ∼ ξ < ∼ 1.01.…”
mentioning
confidence: 98%
“…Constraint from the primordial nucleosynthesis [40] cannot be obtained since the value of a primordial cosmological magnetic vector potential cannot be assessed at present. In addition, constraint from disappearance of bound neutrons in nuclei [41] would need for a rigorous expression of the swapping probability in this case.…”
Section: Variable-collision-rate Experimentsmentioning
confidence: 99%
“…[39]). As a result, ultracold neutron experiments appear as a relevant approach to constrain g (Some other possibilities are not considered for obvious reasons 5 [40,41]). …”
Section: Constraints On G and ηmentioning
confidence: 99%
“…(10) holds over the entire remainder, typically 0.01 − 0.1 s, of the motion to the next TP where p(t) is "measured". Equation (10) shows that the result depends only on the local field variables Ω(t) and ω L (t). It does not depend on the path history; from (9), only the phase −iΘ/2 of β(t) does.…”
Section: Semi-classical Approachmentioning
confidence: 99%
“…At present, we are confronted by an apparent discrepancy of about three standard deviations between the average τ n from ultracold neutron (UCN) storage experiments and the τ n from cold neutron beam experiments as outlined in the next paragraph. It is the leading source of uncertainty in predictions of the primordial abundance of 4 He [8][9][10].…”
Section: Introductionmentioning
confidence: 99%